The Principles of the European Public Services Law - Mihaela Tofan; Ana-Maria Bercu (CES Working Papers, 2009)
European civil service law has emerged as an independent law branch relatively recently. At the EU level there were three categories of rules that regulate the public employees' activity, according tothe treaty type that established one of the top three communities (ECSC, EEC, EURATOM). Following legislative changes that occurred in 1968, it was made a unification of these provisions, resulting in acommon law text for all the officials, known as The Status. Statutory provisions within the field recognize the law principles common to the entire Community law, such as the principle of subsidiarity, but also a number of new principles, based on this area of research, such as officials business efficiency principle, function stability principle etc. Romanian legislation, although relatively new comparing the laws of other states, has taken over many of theseprinciples, being aligned with union provisions in this field.
Keywords: 330; community law; public service; regulation; legal framework; democracy; law principle